2010
DOI: 10.4103/0970-0218.69272
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing utilization of ASHA services under NRHM in relation to maternal health in rural Lucknow

Abstract: Background:Under National Rural Health Mission (NRHM), ASHA (accredited social health activist) has been identified as an effective link to address the poor utilization of maternal and child health (MCH) services by rural pregnant women.Objective:To study the factors influencing utilization of ASHA services in relation to maternal health.Study Design:Cross-sectional.SettingPrimary Health Centre (PHC), Sarojininagar, Lucknow and its rural field area.Study Period:September 2007 to August 2008.Study Unit:RDW (rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 0 publications
4
36
1
1
Order By: Relevance
“…This result was higher than studies conducted in Yem Special Wereda which is 28.5% and in Afar Assayeta which was 73% antenatal care utilization [7,8].…”
Section: Discussioncontrasting
confidence: 60%
“…This result was higher than studies conducted in Yem Special Wereda which is 28.5% and in Afar Assayeta which was 73% antenatal care utilization [7,8].…”
Section: Discussioncontrasting
confidence: 60%
“…11 This is in contrast to other similar studies where maximum were illiterate. 12,13 This may be due to improvement in literacy rate in Tripura over the time. In the present study about 87% of the women had adequate antenatal checkup which is much higher than NFHS-3 (2005-06), 8 Singh et al, 13 Ranjan Das et al 14 and Sunder Lal et al 15 This may be attributed to the higher literacy as well as better working of ASHA in this region.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 This may be due to improvement in literacy rate in Tripura over the time. In the present study about 87% of the women had adequate antenatal checkup which is much higher than NFHS-3 (2005-06), 8 Singh et al, 13 Ranjan Das et al 14 and Sunder Lal et al 15 This may be attributed to the higher literacy as well as better working of ASHA in this region. In this study out of total pregnancy registrations 70% were early; whereas Ranjan Das et al 14 found it to be only 57.2% and Sunder Lal et al 15 found to be 95%.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons given by those who had irregular visits were that they were unaware of the services, non-accessibility to the facility and financial problems. This was much higher than NFHS-3 (2005-06) and Singh et al (12) …”
Section: Discussionmentioning
confidence: 63%